Smart Lane Following and Mobile Controlled Robotic Car - Umesh Pinjarkar; Hitesh Raktade; Saurabh Popalghat; Vishakha Polas; Aayush Kadam (International Journal of Advanced Control and System Engineering, 2024)
One major development in autonomous vehicle technology is the emergence of mobile-controlled robotic cars and smart lane-following vehicles. To improve user control and vehicle autonomy, these systems integrate mobile technology, computer vision, and machine learning. This review work highlights the potential of mobile-controlled and smart lane-following robotic automobiles to transform transportation and related sectors by examining their design, functioning, applications, and obstacles. Autonomous driving relies heavily on smart lane-following technology, which allows cars to maintain their lane boundaries without the need for driver interaction. Furthermore, the incorporation of mobile control facilitates remote interaction and direction of these vehicles by users. This assessment covers the future directions, existing applications, and technological underpinnings of robotic cars that can follow a smart lane and be directed by a mobile device.
Keywords: Computer vision; Machine Learning; mobile technology; robotic automobiles; smart lane